Conscious Level Assessment in Infants - J Gordon Millichap (Pediatric Neurology Briefs)
Neurosurgeons at the Adelaide Children’s Hospital, King William Street, North Adelaide, SA 5006, Australia have used a paediatric version of the Glasgow Coma Scale since 1977 for assessing conscious level in infants and young children.